2016
DOI: 10.1096/fj.201600969r
|View full text |Cite
|
Sign up to set email alerts
|

Loss of scleraxis in mice leads to geometric and structural changes in cortical bone, as well as asymmetry in fracture healing

Abstract: Scleraxis (Scx) is a known regulator of tendon development, and recent work has identified the role of Scx in bone modeling. However, the role of Scx in fracture healing has not yet been explored. This study was conducted to identify the role of Scx in cortical bone development and fracture healing. Scx green fluorescent protein-labeled (ScxGFP) reporter and Scx-knockout (Scx-mutant) mice were used to assess bone morphometry and the effects of fracture healing on Scx localization and gene expression, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…166 The Scx+Sox9+ lineage persist in the adult enthesis and periosteum 164 and contribute to tendon and fracture healing. 164,[168][169][170]…”
Section: Scx+sox9+ Progenitorsmentioning
confidence: 99%
“…166 The Scx+Sox9+ lineage persist in the adult enthesis and periosteum 164 and contribute to tendon and fracture healing. 164,[168][169][170]…”
Section: Scx+sox9+ Progenitorsmentioning
confidence: 99%
“…For example, with developments in molecular biology, an increasing number of genes and biological processes have been found to be associated with fracture healing, and the subsequent emergence of corresponding small bioactive molecules may assist in the treatment of fracture nonunion. Previous evidence suggests that Scx may be involved in the periosteal response during fracture healing ( 3 ). Fischerauer et al ( 4 ) demonstrated that bone morphogenetic protein receptor, type IA (BMPR1A) was upregulated in the growth plate of the fractured tibia, and Morgan et al ( 5 ) found that a BMPR1Aantagonist affected cartilage and bone formation during fracture healing.…”
Section: Introductionmentioning
confidence: 99%
“…Scleraxis (Scx), a member of the Twist-family of basic helix-loop-helix (HLH) transcription factors, is required for tenogenesis. This factor is shown to be critical for the development of functional tendons because it regulates tenocyte specific factors such as tenomodulin (Tnmd) and proteoglycans [33][34][35]. Scx directly transactivates Tnmd via preferential binding to specific DNA sequences via E-boxes such as SCX/E12 or SCX/E47 heterodimers [36].…”
Section: The Impact Of Mechanical Loadingmentioning
confidence: 99%